TEKNIK IMOTILISASI IKAN KERAPU CANTANG (Epinephelus sp.) MENGGUNAKAN EKSTRAK DAUN KECUBUNG (Datura metel L.) - Akbar, Rusdi; Jumsurizal, Jumsurizal; Putri, R. Marwita Sari (Marinade, 2021)
The immotilization technique of cantang grouper (Epinephelus sp.) Using Datura metel L. leaf extract. The purpose of this study was to find the best concentration at onset time of Datura metel L. leaves as anesthetic agent for grouper (Epinephelus sp.) And its survival rate. The results of the study, using extracts of natural anesthetic ingredients of amethyst leaves with concentrations of 20%, 25%, and 30% had different effects (P <0.05) on the onset time and recovery of grouper fish. In this study, it provides a life passing rate of 100% at concentrate 20%, and 25%, while concentrate 30% has a 66.67% survival rate. The best concentration in this study was concentrate 30%, with an onset time of 32.07 minutes with a recovery time of 9.07 minutes. This study used a non-factorial completely randomized design (CRD).